Morphological reading of dry facades in residential buildings (a case study of residential buildings in the western part of Shemiranat district of Tehran) - Alireza Naseri; Leila Zare (طراحی و برنامه ریزی در معماری و شهرسازی, 2025)
The facade of the building is one of the most important components of the building, and the abundance of residential buildings compared to other uses make the main face of the city. People's daily use of residential buildings makes the facade important in these types of buildings; Because a two-way relationship is created between man and the facade in the residential building and both influence each other. In recent years, new materials have been used in the facade, which are different from traditional materials in execution and materials. The aim of the current research is to compare traditional facade materials and new materials from different aspects. The method of the current research is comparative-adaptive, which first included a validity questionnaire with a statistical population of 100 people; to measure people's opinions about the appearance of buildings and types of materials; It was found that most people are interested in knowing more about materials and new implementation methods so that their knowledge about new facades can be improved and they can use this type of materials. In the next step, the residential buildings in the western part of Shemiranat area of Tehran city were examined to determine what kind of materials are used for the facade of the buildings under construction. The result is as follows that out of 97 buildings under construction, new materials are used in the facade of 62 of them. In the next stage of the research, the facade materials of the residential buildings were identified and the two traditional materials of Trautton stone and brick facade were compared with the modern materials of fiber cement board [1], curtain wall [2] and ceramic facade. The result indicates that the dry execution technique consumes less water than the mortar method.